Technologies for Separation of ‘X’ and ‘Y’ Spermatozoa in Bovines: An Overview - Sharma, Prachi; Hadiya, Kamlesh K; Arya, Damini (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Several approaches to sperm sexing such as Albumin gradient, Identification of H-Y antigen, Free-flow electrophoresis, Detection of sex-specific proteins, Centrifugal counter current distribution, Volumetric differences, Percoll density gradient, Flow-cytometry, Laser ablation, etc were put forward by the scientists. However, the alteration in DNA content between X- and Y-sperm remains the key and only discriminating feature for sperm sorting based on which only Flow cytometry and Laser ablation techniques are being used commercially. Flow cytometry is based on precise staining of the DNA of sperm with the nucleic acid-specific dye, Hoechst 33342, to differentiate between the subpopulations of X- and Y-sperm. The fluorescently stained sperm are then sex-sorted using a specialized highspeed sorter. Laser ablation (LA) is a system and method for sorting a mixture of stained particles in a fluid flow path. The system and method includes an electromagnetic radiation source for exciting fluorescence emissions from the stained particles, a photodetector for detecting the fluorescence emissions, a processor for classifying the stained particles, and a photo-damaging laser for damaging selected particles in the flow path.